GE_GERICHTE P/12569/2017 vom 29. April 2020 - GE Cour de justice (2020)
LÉSION CORPORELLE GRAVE;ACCIDENT DE LA CIRCULATION;NÉGLIGENCE;LIEN DE CAUSALITÉ;TORT MORAL;DÉFENSE D'OFFICE;CYCLE | CP.125; CP.12.al3; CPP.122; CPP.126.al2.letb; CPP.135; CPP.426; CPP.428; CPP.433; LCR.26.al1; LCR.31.al1; LCR.32.al1; LCR.34.al1; LCR.41; LCR.43.al2; LCR.46.al1; LCR.58; LCR.59; LCR.90; OCR.3.al1; OCR.4.al1; OCR.30; OCR.40.al3; OETV.216.al1; OETV.217